Chemical component (alcohol-benzene solubles) of various palm fronds-oil palm, date palm and coconut palm / Mohamed Fazarudin Abdul Aziz - Abdul Aziz, Mohamed Fazarudin (2001)
The determine of chemical properties of various palm fronds were determined using methods in TAPPI Standard and the results were discusses in this paper. According to the various species of Oil Palm (Eleaisis guineensis) Fronds, Date Palm (Phoenix dactylifera) fronds and Coconut Palm (Cocos nicifera) fronds was selected as a main material in this study. The experiment was carried out to known the percentage of dissolved components in each palms species. The chemical properties result have shown the alcohol-benzene solubility was for oil palm fronds (18.56%), date palm fronds (18.75%) and coconut palm fronds (18.12%). However, this studies must be continues for the next time for other chemical constituents.